Investigating the effects of context, visual working memory, and inhibitory control in hybrid visual search - Barbosa, Alessandra; Ruarte, Gonzalo; Ries, Anthony J.; Kamienkowski, Juan E.; Ison, Matias J. (Frontiers in Human Neuroscience, 2024)
In real-life scenarios, individuals frequently engage in tasks that involve searching for one of distinct items stored in memory. This combined process of visual search and memory search is known as hybrid search. To date, most hybrid search studies have been restricted to average observers looking for previously well-memorized targets in blank backgrounds. Here we investigated the effects of context and the role of memory in hybrid search by modifying the task's memorization phase to occur in all-new single trials. Additionally, we aimed to assess how individual differences in visual working memory capacity and inhibitory control influence performance during hybrid search. In an online experiment, 110 participants searched for potential targets in images with and without context. A change detection and go/no-go task were also performed to measure working memory capacity and inhibitory control, respectively. We show that, in target present trials, the main hallmarks of hybrid search remain present, with a linear relationship between reaction time and visual set size, and a logarithmic relationship between reaction time and memory set size. These behavioral results can be reproduced by using a simple drift diffusion model. Finally, working memory capacity did not predict most search performance measures. Inhibitory control, when relationships were significant, could account for only a small portion of the variability in the data. This study provides insights into the effects of context and individual differences on search efficiency and termination.